FROM THE PARADIGM OF SEEING TO THE TOUCH PARADIGM: THE BECOMING HAPTIC IN THE CONTEMPORARY ARTISTIC CREATION - Silva, Salif (European Scientific Journal, ESJ, 2014)
The haptic perception claims a central place in the interactive experience. The interactive art is tactile art by definition. This paper aims to deepen the relationship between the haptic perception and the media art, reinforcing the relationship between the user and interfaces, as well as the tactile attribute of that experience where the user acts and updated artwork; Explore the meaning of the tactile sense for our experience and understanding of the world; Questioning the primacy of the visual experience and the rhetoric of ocularcentrism, combining three elements: the haptic perception, the field of media art, and phenomenological thought of Merleau-Ponty; What is the role of haptic perception towards the intensification of sensory stimuli of digital culture? This is a question about interfaces and the becoming haptic in the experience of art, not as an aesthetic trend in general, but as a possibility of the art.